Slovenian Complementary Health Insurance as a Service of General Economic Interest - Bruno Nikolić (Central European Public Administration Review)
Slovenian legislation defines complementary health insurance as an activity of the public interest, which represents an inseparable and essential element of healthcare system and as such pursues objectives identical to those of compulsory health insurance – financial security of population against high healthcare expenses and appropriate and fair access to efficient and quality healthcare. EU Member States often introduce different regulatory measures to safeguard the public interest in the field of economic activities. These measures often contravene the Union acquis (the rules on the functioning of the internal market and competition law), which is in principle unacceptable. This article aims to define Slovenian complementary health insurance as a service of general economic interest, which opens up new prospects for the Member States’ adoption of the regulatory measures that are not compliant with the rules on the functioning of the internal market and EU competition law.